2022
DOI: 10.3390/cryst12101488
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Characteristics of High-Chromium Based Multi-Component White Cast Irons

Abstract: It has been evaluated the relationship between the microstructure and three-body abrasive wear behavior of high-chromium (18 and 27 mass % Cr) based (3 mass % each of V, Mo, W, and Co) multicomponent white cast iron materials (high-Cr MWCIs). It was also compared to MWCI to determine the service life of the materials. The results indicate that the microstructure of the material is composed of mainly martensite matrix and different types of precipitated carbides. The wear resistances of both the high-Cr MWCIs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…The relatively low wear resistance of the alloys studied is primarily associated with their cast state. In this state, as it was established earlier [55], the matrix alloy is subject to intense wear, and the primary crystals of (Fe,Cr) 7 C 3 carbide are subject to destruction. This regularity in the destruction of the contact surface was confirmed in all cases in a metallographic study of the wear surface of experimental samples.…”
Section: Wear Resistancementioning
confidence: 73%
See 1 more Smart Citation
“…The relatively low wear resistance of the alloys studied is primarily associated with their cast state. In this state, as it was established earlier [55], the matrix alloy is subject to intense wear, and the primary crystals of (Fe,Cr) 7 C 3 carbide are subject to destruction. This regularity in the destruction of the contact surface was confirmed in all cases in a metallographic study of the wear surface of experimental samples.…”
Section: Wear Resistancementioning
confidence: 73%
“…The phase analysis performed showed that the samples of castings made of G-X300CrMo27-1 cast iron (3.75 wt%) crystallized under the above conditions, were formed mainly by the following phases of α-iron, Cr 7 C 3 ((Fe,Cr) 7 C 3 ), Fe 3 C, Fe 4 C и Cr 2 C (M 2 C) after TTM at all temperatures. It is typical for cast irons of the composition studied [54,55]. Comparison of the diffraction patterns of castings after TTM in the solid-liquid (1260 and 1300 °С) and liquid state (1380 °С) indicates (figure 9) that there is a significant change in the intensity of the peaks of the (Fe,Cr) 7 C 3 and Cr 2 C (M 2 C) phases depending on the TTM modes.…”
Section: Phase Analysismentioning
confidence: 91%
“…In general, the destabilization heat treatment of MWCI occurs as the alloy is heated at 1173-1423 K for several hours and is then quenched using the air-force-cooling method. The process is continued during the tempering process, where the alloy is re-heated at 693-813 K and then cooled using the air-force-cooling method [30][31][32]. Therefore, all the alloys were pre-heated at 1323 K for one hour and then As previously explained, the austenite matrix transforms into martensite during the heat treatment process, which effectively increases the strength and wear resistance of the alloy.…”
Section: Preparation Of Alloysmentioning
confidence: 99%
“…In previous studies [17], we also found (Fe 3.27 Cr 2.99 W 0.74 ) C 3 carbides in high-chromium cast iron coating. Purba et al [18] evaluated the relationship between the microstructure and three-body abrasive wear behavior of high-chromium-based (V, Mo, W and Co) multicomponent white cast iron materials. These studies showed that multielement doping can form multicomponent compounds, effectively improving the wear resistance of high-chromium cast iron.…”
Section: Introductionmentioning
confidence: 99%